VARIATION FIGURES OF SPEECH IN THE WEBTOON DEDES WORKS EGISTIGI ITS RELEVANCE AS A LEARNING MATERIAL FOR INDONESIAN LITERATURE: VARIASI MAJAS DALAM WEBTOON DEDES KARYA EGISTIGI RELEVANSINYA SEBAGAI BAHAN PEMBELAJARAN SASTRA INDONESIA - Dinda Cholifah; Atiqa Sabardila (LLDIKTI Wilayah X, 2024)
This research aims to identify the use of figures of speech in the Dedes webtoon and its relevance as teaching material in terms of its appropriateness. This research is a qualitative descriptive study using the matching method and referential sorting techniques in data analysis. The object of this data is 47 episodes of the Dedes webtoon. The research subjects are words, sentences, monologues, dialogues which contain the use of figures of speech in them. Based on the research conducted, there are the utilizations of figure of speech in the Dedes webtoon including hyperbole, metaphor, simile, personification, sarcasm, litotes, allusion, allegory, antonomasia, metonymy, eclamation, and correction. Figures of speech in the Dedes webtoon can be integrated into learning by making it a KD 3.9 teaching material regarding analyzing novel structures and linguistic elements in class XII, as well as making the webtoon an interactive medium for learning in the digital era.